SENI KALIGRAFI SEBAGAI MEDIA DAKWAH DAN PENDIDIKAN ISLAM - Rika Ananda Yunisa; Jihan Hijrahani Azizah Brutu (Jurnal Ekshis, 2025)
The art of calligraphy is the art of beautiful writing which is one of the characteristics of Islamic art. The art of calligraphy not only has aesthetic value, but also the value of worship and preaching. This research aims to examine the role and function of calligraphy art as a medium for Islamic da'wah and education in Indonesia. The research method used is a qualitative method with a descriptive analytical approach. Research data was obtained from literature studies. The research results show that the art of calligraphy has an important role in conveying Islamic messages, enriching the treasures of Islamic art and culture, and increasing the appreciation and creativity of Muslims. The function of calligraphy art as a medium for Islamic da'wah and education includes educative, informative, motivational, inspirational and transformative functions.